A biostimulant prepared from red seaweed Kappaphycus alvarezii induces flowering and improves the growth of Pisum sativum grown under optimum and nitrogen-limited conditions - Shukla, Pushp Sheel; Nivetha, Nagarajan; Nori, Sri Sailaja; Kumar, Sawan; Critchley, Alan T.; Suryanarayan, Shrikumar (Frontiers in Plant Science, 2024)
Nitrogen (N) is one of the critical elements required by plants and is therefore one of the important limiting factors for growth and yield. To increase agricultural productivity, farmers are using excessive N fertilizers to the soil, which poses a threat to the ecosystem, as most of the applied nitrogen fertilizer is not taken up by crops, and runoff to aquatic bodies and the environment causes eutrophication, pollution, and greenhouse gas emissions. In this study, we used LBS6, a Kappaphycus alvarezii-based biostimulant as a sustainable alternative to improve the growth of plant under different NO3 -fertigation. A root drench treatment of 1 ml/L LBS6 significantly improved the growth of Pisum sativum plants grown under optimum and deficient N conditions. No significant difference was observed in the growth of LBS6-treated plants grown with excessive N. The application of LBS6 induced flowering under optimum and deficient N conditions. The total nitrogen, nitrate and ammonia contents of tissues were found to be higher in treated plants grown under N deficient conditions. The LBS6 treatments had significantly higher chlorophyll content in those plants grown under N-deficient conditions. The root drench application of LBS6 also regulated photosynthetic efficiency by modulating electron and proton transport-related processes of leaves in the light-adapted state. The rate of linear electron flux, proton conductivity and steady-state proton flux across the thylakoid membrane were found to be higher in LBS6-treated plants. Additionally, LBS6 also reduced nitrogen starvation-induced, reactive oxygen species accumulation by reduction in lipid peroxidation in treated plants. Gene expression analysis showed differential regulation of expression of those genes involved in N uptake, transport, assimilation, and remobilization in LBS6-treated plants. Taken together, LBS6 improved growth of those treated plants under optimum and nitrogen-limited condition by positively modulating their biochemical, molecular, and physiological processes.